Pre‐admission beta‐blocker therapy and outcomes in cardiogenic shock: Insights from the Altshock‐2 Registry - Matteo Pagnesi; Mauro Riccardi; Alice Sacco; Giovanni Tavecchia; Giovanna Viola; Simone Frea; Martina Briani; Letizia Fausta Bertoldi; Maurizio Bertaina; Luciano Potena; Serafina Valente; Marco Marini; et al. (ESC Heart Failure, 2025)
Abstract Aims We aimed to assess the impact of pre‐admission beta‐blocker (BB) therapy on the clinical characteristics, in‐hospital treatment and outcomes of patients with cardiogenic shock (CS). Methods All patients enrolled in the multicentre prospective Altshock‐2 registry since March 2020 with available data on pre‐admission BB therapy were included. Clinical characteristics, in‐hospital management, haemodynamic parameters and clinical outcomes were compared in patients with versus without BB therapy. The primary endpoint was in‐hospital mortality. Results A total of 668 patients were included [median age 66 (56–74) years, male sex 76.5%]: 299 patients (44.8%) with and 369 patients (55.2%) without previous BB therapy. Patients receiving pre‐admission BB therapy had more frequently heart failure‐related CS (43.8% vs. 17.9%) and less frequently cardiac arrest at presentation (20.1% vs. 27.8%, P = 0.027). Levosimendan was used less frequently and dobutamine was used more frequently in patients with baseline BB therapy (P = 0.033 and P = 0.043, respectively). Differences in the early haemodynamic response to vasoactive drugs were observed between patients with and without previous BB therapy, with a significant impact of baseline BB on mean arterial pressure (MAP) response during norepinephrine infusion (P = 0.012) and with dobutamine having a reduced response in MAP and heart rate in patients receiving BBs before admission (P = 0.023 and P = 0.001, respectively). In‐hospital mortality was not significantly different between the BB and no‐BB groups (40% vs. 33.7%; adjusted odds ratio 1.32, 95% confidence interval 0.84–2.07, P = 0.224). Similarly, baseline BB therapy was not independently associated with 48 h mortality (12.7% vs. 14.6%; adjusted odds ratio 1.09, 95% confidence interval 0.64–1.87, P = 0.749). The lack of association between baseline BB therapy and mortality was also confirmed at inverse probability of treatment weighting‐adjusted analysis. Conclusions In a real‐world, contemporary cohort of patients with CS, previous BB therapy influenced the haemodynamic response to vasoactive drugs, but it was not associated with in‐hospital mortality.